2016
DOI: 10.1038/ncomms11838
|View full text |Cite
|
Sign up to set email alerts
|

Nanoreporter PET predicts the efficacy of anti-cancer nanotherapy

Abstract: The application of nanoparticle drug formulations, such as nanoliposomal doxorubicin (Doxil), is increasingly integrated in clinical cancer care. Despite nanomedicine's remarkable potential and growth over the last three decades, its clinical benefits for cancer patients vary. Here we report a non-invasive quantitative positron emission tomography (PET) nanoreporter technology that is predictive of therapeutic outcome in individual subjects. In a breast cancer mouse model, we demonstrate that co-injecting Doxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 29 publications
3
103
0
Order By: Relevance
“…Recent work by Pérez-Medina et al have used a PET nanoreporter technology to demonstrate that PET-radiolabeled nanoparticles can predict the efficacy of nanomedicinal therapies in animal models. 22 Hence, we foresee that the method described here may provide a powerful developmental theranostic tool for many current and future liposomal drugs and will allow the study of their biodistribution prior to treatment for patient selection. We expect this work may facilitate the inclusion of a pretreatment (and possibly on-treatment) imaging stage for the improvement of the clinical value of liposomal drugs that encapsulate metal-chelating drugs.…”
Section: Discussionmentioning
confidence: 97%
“…Recent work by Pérez-Medina et al have used a PET nanoreporter technology to demonstrate that PET-radiolabeled nanoparticles can predict the efficacy of nanomedicinal therapies in animal models. 22 Hence, we foresee that the method described here may provide a powerful developmental theranostic tool for many current and future liposomal drugs and will allow the study of their biodistribution prior to treatment for patient selection. We expect this work may facilitate the inclusion of a pretreatment (and possibly on-treatment) imaging stage for the improvement of the clinical value of liposomal drugs that encapsulate metal-chelating drugs.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in the phase 3 study of PLD against doxorubicin single agent in metastatic breast cancer, no survival advantage was observed (4) despite the clear superiority of PLD in animal tumor models. Recent studies in mouse models using radionuclide SPECT imaging with In 111 -labeled liposomes and PET imaging with Zr 89 -labeled liposomes admixed with PLD have observed that higher tumor uptake of liposomes correlates with greater antitumor activity at the individual level (44, 45). These studies also show a correlation between tumor uptake and tumor microvessel density and reveal remarkable heterogeneity in liposomal tumor accumulation.…”
Section: Are We Using the Right Clinical Trial Designs And Assessments?mentioning
confidence: 99%
“…[1618] Moreover, nanoparticles radiolabeled with positron emitters can potentially be employed in treatment prognosis and patient selection, aptly demonstrated in a recent study using 89 Zr-labeled nanoreporter for Doxil. [19] Co-injection of the nanoreporter with the clinically approved anti-cancer nanodrug Doxil was able to predict the therapeutic outcomes based on the tumor uptake in a murine breast cancer model. While still in preclinical settings, such systems hold promise for clinically relevant cancer management in the future.…”
Section: Nanotechnology In Positron Emission Tomography: An Emergimentioning
confidence: 99%